Analysis of the Effect of Grooving the Flow Passage on the Flow Characteristics of the Fluid Passing Through the Cylindrical with a Rotating Cylinder - Hassani , Meysam; Ebrahimi , Mahmood; Rahmani , Masoud; Moslemi Petrudi, Amin; Scurtu , Ionut Cristian (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Screw compressors belong to the group of positive displacement machines, which are widely used in various industries due to the advantages of these compressors compared to other industrial compressors. The distance between the moving and fixed parts of the rotating equipment is inevitable. This distance causes current leakage in all types of compressors, which reduces the efficiency of the compressor. In this research, the effect of grooving the flow passage on the flow characteristics of the passing fluid has been investigated using ANSYS CFX software. The simulation quality of positive displacement machines strongly depends on the correct prediction of the leakage current between the existing switches. It seems that creating a groove in the path of the passing current increases the thickness of the boundary layer, which acts as a barrier against the return leakage current between the rotor and the stator in the compressor. In this paper, a simplified model of the problem, which is a grooved cylinder in which a piston rotates, is investigated. First, the flow of fluid from a cylinder whose inner surface is smooth is examined, and then in boundary conditions and similar geometric dimensions, the effect of different types of grooves with different geometries on the flow characteristics will be studied. The variable is the change in drag force on the inner surfaces of the cylinder. The results show that in the best case, ie a cylinder with a single helical groove, the drag force compared to smooth geometry is 1.79 times and the flow rate is reduced by 13.21%. It is expected that the results of this study can be generalized to reduce leakage current between the rotor and the screw compressor housing.